190k views
0 votes
Solve x2 − 4x − 1 = 0 by completing the square.

Solve x2 − 4x − 1 = 0 by completing the square.-example-1
User Shautieh
by
5.5k points

1 Answer

3 votes

Hello! To solve completing by the square, we have to follow some steps:


\begin{gathered} x^2-4x=1 \\ \end{gathered}

Now, we have to add the same value in both sides (square):

If we factorize the first part of this expression, we can obtain:

Notice that we obtained the same expression, and now we know the value of the square. So, let's rewrite the first expression and replace the squares by 4:

Solve x2 − 4x − 1 = 0 by completing the square.-example-1
Solve x2 − 4x − 1 = 0 by completing the square.-example-2
Solve x2 − 4x − 1 = 0 by completing the square.-example-3
Solve x2 − 4x − 1 = 0 by completing the square.-example-4
User David Coggins
by
4.9k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.